2013
DOI: 10.1111/j.1540-4781.2013.12008.x
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Gesture in Lexically Focused L2 Instructional Conversations

Abstract: The purpose of the present study is to investigate the mediational function of the gesture–speech interface in the instructional conversation that emerged as teachers attempted to explain the meaning of English words to their students in two EFL classrooms in the Ukraine. Its analytical framework is provided by Vygotsky's sociocultural psychology (e.g., Lantolf & Thorne, 2006) and McNeill's (1992, 2005) theory of gesture–speech synchronization, in particular his notion of catchment—recurrent gestural features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 48 publications
1
43
0
1
Order By: Relevance
“…Considered in conjunction with work showing that gesture production facilitates L2 acquisition in classroom and naturalistic conversational settings (Adams, 1998;Smotrova & Lantolf, 2013;van Compernolle & Williams, 2011), the findings suggest that encouraging participants to gesture when learning novel L2 words in laboratory settings, as well as in classroom settings, may enhance their acquisition of these words more than simply allowing them to view gestures in conjunction with target words. The relationships between gestures and verbal explanations of L2 word meanings also suggest that the intrinsic variability and interactivity of classroom and conversational settings, which allow for spontaneous verbal exchanges, may be conducive to L2 word learning.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Considered in conjunction with work showing that gesture production facilitates L2 acquisition in classroom and naturalistic conversational settings (Adams, 1998;Smotrova & Lantolf, 2013;van Compernolle & Williams, 2011), the findings suggest that encouraging participants to gesture when learning novel L2 words in laboratory settings, as well as in classroom settings, may enhance their acquisition of these words more than simply allowing them to view gestures in conjunction with target words. The relationships between gestures and verbal explanations of L2 word meanings also suggest that the intrinsic variability and interactivity of classroom and conversational settings, which allow for spontaneous verbal exchanges, may be conducive to L2 word learning.…”
Section: Discussionmentioning
confidence: 74%
“…This prompts their interlocutors to suggest appropriate completions, sometimes while producing similar gestures themselves (McCafferty, 2002;Mori & Hayashi, 2006). Similarly, there is evidence from classroom research that L2 learners spontaneously produce representational gestures to convey aspects of L2 word meaning that they cannot express verbally (Smotrova & Lantolf, 2013). This research showed that instructors utilized learners' spontaneous gestures by integrating them into their corrective feedback, and learners reused the gestures in conjunction with corrected target language speech, demonstrating improved understanding.…”
mentioning
confidence: 82%
“…Gesture studies are gradually becoming more prominent in the field of SLA (Lantolf 2010;McCafferty 2004McCafferty , 2006McCafferty and Stam 2008;Smotrova and Lantolf 2013). A growing number of studies on language, cognition, and thinkingfor-speaking have also analyzed how path and/or manner of motion is conveyed through gesture in motion events (Brown 2015;Hendriks and Hickmann 2015;Brown and Gullberg 2008;Choi and Lantolf 2008;Chui 2011;Gullberg et al 2008;McNeill, 2001;Özyürek, et al 2008;Pavlenko and Volynski 2015).…”
Section: Sociocultural Theory Gesturing and Motion Eventsmentioning
confidence: 96%
“…Teachers naturally use gestures to teach the meaning of new words, and these form an important component of comprehensible input for learners (Smotrova & Lantolf, 2013). In addition to helping with meaning, a more explicit use of gestures can help learners retain the phonological form of words.…”
Section: Gestures In L2 Vocabulary Learningmentioning
confidence: 99%